A large Rab GTPase family in a small GTPase world. (2nd January 2017) - Srikanth, Sonal; Woo, Jin Seok; Gwack, Yousang
ABSTRACT: More than 60 Rab GTPases exist in the human genome to regulate vesicle trafficking between organelles. Rab GTPases are members of the Ras GTPase superfamily that broadly control budding, uncoating, motility and fusion of vesicles in most cell types. Rab proteins interconvert between active, GTP-bound form and inactive, GDP-bound form. In their active conformation, they interact with various effector molecules to carry out diverse functions. Rab GTPases are usually small containing only a GTPase domain with a C-terminal prenylation site for membrane anchoring. Recently, we identified a large G protein, CRACR2A (CRAC channel regulator 2A), which uncovers novel functions of Rab GTPases. First, CRACR2A encodes a large Rab GTPase containing multiple functional domains contrary to small Rab GTPases. Second, CRACR2A plays an unexpected role in regulating intracellular signaling pathways important for T cell activation, unlike the canonical role of small Rab GTPases. Vesicles containing CRACR2A bud out from the proximal Golgi area and translocate into the immunological synapse to activate these signaling pathways. Third, instead of recycling, CRACR2A is consumed by a unidirectional pathway. These events are sequentially regulated by prenylation, GTP binding, protein interaction with a signaling adaptor Vav1, and degradation. Together, our findings reveal a novel function of a large Rab GTPase in intracellular signaling pathways, which may be shared by other large Rab GTPases, Rab44 and Rab45.